Study on Engagement Performance of Engagement Sleeve and Engagement Gear Ring of Without Synchronizer Transmission - Cui Wenxia; Zhang Ruiliang; Zhang Bo (Jixie chuandong)
In order to study the engagement performance of engagement sleeve and engagement gear ring in the shifting process of without synchronous AMT transmission mounted on hybrid vehicle, improve the smoothness of gear shifting and shorten the shifting time, the theoretical analysis and the virtual prototype simulation analysis method are used to study the engagement process between engagement sleeve and engagement gear ring of AMT transmission. The engagement process is divided into four stages: free sliding stage, tooth tip collision stage, tooth tip friction stage and inter-tooth meshing stage, a mathematical model is established. The dynamics model of the engagement process is established by Adams. The simulation model is compared with the theoretical calculation value, and the error is 7.3%. The effects of the speed difference between the meshing sleeve and the engagement gear ring and the shift force acting on the meshing sleeve on the meshing process are studied, and the optimum range of the speed difference is obtained. The research results of the study can provide critical guidance for automatic shift control.